DIFFERENCES BETWEEN FOREHEAD AND BACK OF THE HAND TEMPERATURE MEASUREMENTS USING NON-CONTACT INFRARED THERMOMETERS IN HEALTHY YOUNG ADULTS - Rendri Bayu Hansah; Gusti Muhammad Dimas; Kurnia Maidarmi Handayani; Widia Sari; Annisa Lidra Maribeth; Lieka Nugrahi Jaslindo (Yayasan Nusantara Hasana Berdikari, 2026)
The COVID-19 pandemic necessitated the implementation of rapid, safe, and non-invasive body temperature screening methods to facilitate early identification of potentially infectious individuals. Non-contact infrared thermometers have therefore been widely adopted for this purpose. However, concerns have been raised regarding the accuracy of temperature measurements obtained from different anatomical sites, particularly in the context of increased reliance on alternative measurement locations such as the back of the hand (dorsum manus regio). This study aimed to compare body temperature measurements obtained from the forehead and dorsum manus using a non-contact infrared thermometer, with axillary temperature measured by a digital thermometer as a reference. An analytical observational study with repeated measures was conducted among 70 third-year medical students at Universitas Baiturrahmah. Temperature measurements were performed at the forehead, dorsum manus, and axilla, and participants were divided into control and intervention groups based on environmental measurement conditions. Repeated measures ANOVA revealed significant differences between forehead temperature and both dorsum manus and axillary temperatures, while no significant difference was observed between dorsum manus and axillary measurements. Independent t-tests showed no significant differences between control and intervention groups. These findings suggest that dorsum manus temperature measurements may approximate axillary values under stable conditions in healthy young adults, although caution is required when generalizing to other populations or clinical settings.